Relationship between dog culling and incidence of human visceral leishmaniasis in an endemic area - Nunes, Caris Maroni [UNESP]; Pires, Marina Mota [UNESP]; da Silva, Karinne Marques [UNESP]; Assis, Filipe Daniel [UNESP]; Goncalves Filho, Jesualdo; Venturoli Perri, Silvia Helena [UNESP] (Elsevier B.V., 2010)
Domestic dogs are the main reservoirs of visceral leishmaniasis (VL) in urban areas; one of the control measures adopted in Brazil is the elimination of this reservoir. In order to test the relationship between the euthanasia rate of the canine reservoir and the incidence of the disease in humans, data on dog culling from the Centre for Zoonosis Control of Aracatuba, São Paulo, Brazil, during the period from 1999 to 2008 and visceral leishmaniasis human cases registered in the same period were analyzed. Reduction of human VL incidence was statistically correlated to dog euthanasia rate (P=0.0211; r(2)=0.616) when it was analyzed for the period of two years after application of this measure. Other factors that may influence this relationship are considered. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Occurrence; Canine reservoir; Culling